Spin–orbit torque driven skyrmion motion under unconventional spin Hall effect - Yang Zhao; Dongying Guo; Zhongming Zeng; Maokang Shen; Yue Zhang; Riccardo Tomasello; Giovanni Finocchio; Ruilong Wang; Shiheng Liang (New Journal of Physics, 2022)
The effective control of skyrmion motion is a critical aspect for realizing skyrmion-based devices. Among the potential directions, the use of current induced spin–orbit torque (SOT) is energetically efficient. However, the conventional heavy metals with high crystal symmetry limit the charge-to-spin conversion to the orthogonal configuration, which causes the skyrmions to deflect from the electrical current direction with a finite skyrmion Hall angle. Here, we investigate the SOT driven skyrmion motion under unconventional spin Hall effect. We systematically study the effect of a noncollinear low-symmetry spin source layer with spin moments mixed by Rashba-like S _y , Dresselhaus-like S _x and out-of-plane like S _z on skyrmion features (velocity, diameter and Hall angle) stabilized in a ferromagnet/WTe _2 heterostructure. Our results may provide a new degree of freedom for controlling the skyrmion Hall angle, and can open the way for the discovery of new ferromagnetic multilayer where the skyrmion Hall angle is suppressed by the proper design of different SOT driven forces.